Estudio y propuesta de la infraestructura pecuaria en zonas subtropicales, caso Zamora Chinchipe y su influencia para el mejoramiento de la calidad de vida de los productores pecuarios - Villalta Gualán, Dalton Fabián (2015)
This research entitled "STUDY AND PROPOSED INFRASTRUCTURE LIVESTOCK IN subtropics, Zamora Chinchipe CASE AND HIS INFLUENCE FOR IMPROVING THE QUALITY OF LIFE OF LIVESTOCK PRODUCERS" is based on knowing the importance of livestock infrastructure, the same facilitating the livestock producer to carry out their activities properly and easily. With the information collected as a baseline, the theoretical framework that started with a contextualization of the environment to investigate raising issues as infrastructure in rural areas, building structure diagnosis of each raised infrastructure ensued. For data collection proceeded to apply the methodology was to survey all livestock producers with infrastructure in the province of Zamora Chinchipe, through which it is ultimately determined that there is little infrastructure built and currently it is in disuse it is noted that for bovine milk infrastructure exists, 42.86% meat infrastructure 80%, showing that in the province a significant number have constructions for raising bovine milk, bovine infrastructure and little meat as infrastructure concerning breeding swine 56.52% and 50% of the dedicated infrastructure for fattening pigs, which indicates that they infrastructure composite construction and having a substantial financial investment. In the case of poultry breeding infrastructure is 76.92% and poultry fattening infrastructure 95.45%, which explains why most of the producers in this activity in free areas. Was obtained for fish breeding infrastructure 100% and the infrastructure fattening 79.41%, resulting in that most producers in this activity in the traditional way, then in the case of guinea pig breeding infrastructure 82.61% the infrastructure and guinea pigs for fattening, 82.61%, explains that currently the province of Zamora Chinchipe this activity traditionally takes place and there is no infrastructure consideration.